The Influence And Impact Of The Ai-Based Application Chat Gpt On The Learning Culture Of Corporations - A Case In An Emerging Market - Franciskus Antonius; Mila Yuliani; Safina Meilia (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Employee competency development is the main pillar in the strategy to advance the organization. This research firmly aims to identify the positive impact of implementing a competency development program on improving the quality of employee performance and the level of innovation in the work environment. With the help of ChatGPT's Artificial Intelligence (AI) effectively supports the Learning/Training Development Division team in detailing the competencies required for each position and job code in the company, as well as formulating an appropriate syllabus. The research methodology combines experimental and observational approaches, in-depth interviews, and document analysis by measuring the Key Performance Indicator (KPI) for eight employees of the IT Development Division and then compiling a skills matrix. The study's findings demonstrate that the employee competency development program may identify the technical competency and soft skill requirements of staff members, particularly with regard to leadership, with the help of ChatGPT, an artificial intelligence (AI) platform. This is a benchmark for the success of employee development programs in the company. This research concludes that the employee competency development program using ChatGPT has a significant positive impact on improving performance and innovation in the company. It recommends ongoing program implementation, utilizing current methods that can be adapted to the company's ongoing needs